Competitive electricity markets and the case of California - Davis, Clay D. (Kansas State University, 2008)
The primary purpose of this report is to address the potential benefits and drawbacks of competitive electricity generation. A number of countries have introduced various forms of competition into the electric utility industry. The most notable attempt in the United States and the focus of this report took place in California in the late 1990s. This report is divided into two parts. The first covers the history of the electricity industry by reviewing influential policies, cost of service regulation, and concluding with incentive regulation. The second part discusses the potential benefits and drawbacks of a competitive generation sector, through the lens of the California experiment. Government policies have dramatically changed in the last twenty years. Many of these changes were aimed towards increasing competition within the generation sector and have made a competitive generation sector possible. Whether these policies are correct has been the focus of much debate. A competitive generation sector could potentially operate more efficiently than under traditional regulatory regimes. Whether this potential will be realized is in question. This report assesses this question by looking at the events that took place in California. The competitive wholesale markets in California functioned properly for nearly two years before the events of the "California Electricity Crisis" took place. This showed that a competitive wholesale market is possible once certain criteria are met; most importantly adequate competition to reduce a firm's potential to exercise market power. The "Crisis" in California showed what can happen if these criteria are not satisfied. Nevertheless, there is still much optimism about the potential benefits of competitive electricity markets.
Keywords: California; Electricity; Crisis; Competition; Economics, General (0501)